An excursion into the synthesis of novel flavanones - Mansoor, Rukaya (Department of Chemistry, 2023)
The aim of this project was to develop new methodology for synthesizing flavanones asymmetrically in a manner that could be extended to the synthesis of novel indoloflavanone analogues. The designated approach was via an asymmetric aldol reaction catalysed by a chiral organocatalyst followed by an intramolecular Mitsunobu reaction. Following a review of the existing methodologies for the synthesis of racemic and asymmetric flavanones and various flavan analogues, an initial model reaction between acetophenone and para-nitrobenzaldehyde returned the aldol product using (S)- proline tetrazole as organocatalyst. Several experiments on optimization were conducted to identify the best stoichiometry/conditions as ketone (4): aldehyde (1): catalyst (10%): DMSO (2): H2O (2) at room temperature for three days, which returned the desired aldol product in 64% yield and a pleasing ee of 93%. Interestingly, it was found that the amount of water in the reaction played a role in dictating the stereogenicity of the product. Unfortunately, changing the ketone to the required 2- hydroxyacetophenone for a flavanone synthesis resulted in a very sluggish reaction, delivering the product in a very low conversion (~ 10%) after 3 days. This was attributed to the poor electrophilicity of the ketone carbonyl group in the enamine formation step because of the ortho electron-releasing phenolic hydroxyl group. For increasing the electrophilicity, the approach was changed to using a Knoevenagel condensation reaction between an activated β-ketoester derivative of 2- hydroxyacetphenone and para-nitrobenzaldehyde according to the optimised aldol reaction conditions. Although this successfully delivered chemically the required flavanone precursor with a satisfactory yield (77%), there was no enantioselectivity, which was attributed to either the chiral entity being too far away from the prochiral site or because of an increased rate of iminium ion hydrolysis prior to the oxa-Michael cyclisation step due to the electron-withdrawing ester group. Gratifyingly, however, this methodology could be applied to synthesis of a 2-indolylflavanone (in racemic form) as a B-ring indolylflavanone, setting up a prototype for a future, more detailed study. With regards to A-ring modification, 3-acetyl-2-hydroxyindole and various protected variants were tried out as the acetophenone partner in the methodology only to meet the same problems as described above due to strong electron donation into the carbonyl group. Similarly, we weren't able to extend this to a -ketoester variant via acetyl group C-carboxylation as before. Eventually, the problem was resolved by a C-3 acylation of N-Boc-2-indolone with cinnamoyl chloride, rendering a precursor for indoloflavanone synthesis via oxa-Michael cyclisation. Although the latter was not achieved because of time constraints, this acylation study opens up a novel entry for further study into the synthesis of A-ring indoloflavanones for biological evaluation.